(3cJGH CUhd JQcjH GdCOhjIs - (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe Ef GdhGLH Ydi cd Pi dH Cf jJbQH Edi Gddg JYGdi hdCfi deG cfJ HUOO gPg GdUfGYI CMHHJ Cf CLeY ef cJH GdWH s
(3BNQgG (B:s
(3hJZda Hg GdTYQ SQjYkG bHd Cf jHQO hjJQc MJi jLa hjcQQ Cf GMJjL Edjg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jdjg WQjbI eLQHI dCHi GdHQcGJ GdHZOGOis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs